1980
DOI: 10.2172/5697224
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of radon-222 emissions from underground uranium mines. Progress report No. 2

Abstract: Estimated Radon Emission From Waste Following Closure of the Mines. Piles at Four Mines Estimated Radon Storage Piles Release from Six Mine 10. Estimated Radon Release in Mine Water From Six Mines 11. Relationship Between Radon Emission and Mine Production C.l Distribution of Grab Sampling Times and Associated Biases C.2 lntercomparison of Vent Flow Measurements Using Different Instruments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Their findings corroborate the report of Jackson et al (1980), who estimated that only a very small fraction of the radon released from underground uranium mines in the United States is transported by drainage waters, most of it having already been released into the mine ventilation system. Although we made no attempt to assess the interaction of groundwater and airborne radon transport in the Stripa experimental drifts, it is apparent from our experience that the two are closely related.…”
Section: Introductionsupporting
confidence: 88%
“…Their findings corroborate the report of Jackson et al (1980), who estimated that only a very small fraction of the radon released from underground uranium mines in the United States is transported by drainage waters, most of it having already been released into the mine ventilation system. Although we made no attempt to assess the interaction of groundwater and airborne radon transport in the Stripa experimental drifts, it is apparent from our experience that the two are closely related.…”
Section: Introductionsupporting
confidence: 88%
“…Of course, the abnormal conditions could cause such profound radon concentration changes that they would significantly affect the average. This minimum protocol was followed by Jackson et al (1980) and was evaluated using two systems of continuous sequential monitors and a statistical evaluation of the dispersion of the measurements. While that interpretation indicated that the relative standard deviation of measurements involved in counting scintillation flasks was about 4% when four samples were averaged, the sampling errors appeared to be larger.…”
Section: Grab Sampling and Radon Measurementmentioning
confidence: 99%
“…At a fourth vent, variations caused by cyclic vent shutdowns produced ratios as high as 7.3. While Jackson et al (1980) determined that these variations tended to produce a relatively small error in their measurement of the annual average radon emission from the entire U.S. mining industry, based on grab sample determinations of radon in exhaust air, their effect on the average emission rate determined for a single mine can be substantial. Where possible, a large number of grab samples should be collected so that patterns of emission rates and correlations with operations can be established.…”
Section: Grab Sampling and Radon Measurementmentioning
confidence: 99%
See 2 more Smart Citations